A computer controlled system for earthquake protection of structures. (1st January 2000) - Kaplan, H.; Seireg, A.
This paper investigates the feasibility of developing an active system for the protection of structures against earthquakes. The system is incorporated in a specially designed supporting base. A computer simulation of the system is utilised for selecting the design parameters of the base and the supporting elements. The system is controlled according to pre-programmed rules in order to minimise the forces transmitted to the structure. The inputs to the controller are the signals from appropriately placed off-site seismic detectors. A single degree of freedom structure is considered to represent the fundamental vibratory mode of the structure which is generally responsible for the largest component of its dynamic response to ground excitation. An illustrative example shows that the proposed system is implementable and can result in orders of magnitude reduction in the transmitted force to the structure. It can also minimise the torsional effects resulting from any arbitrary distribution of the mass for non-symmetrical structures.